Ant colony optimization for controller and sensor-actuator location in active vibration control - Md Nor, Khairul Affendy; Abdul Muthalif, Asan Gani; Wahid, Azni N. (2013)
Most of engineering structures are made of simple beams and plates, and these types of structures are easily influenced and excited by external vibration. Piezoelectric material has been a popular choice of sensor and actuator to attenuate vibration actively in flexible structures and numerous techniques of optimal control and actuator placement had been proposed. The main focus of this paper is to find the optimal location of the collocated sensor-actuator and controller gains to actively control vibration, using a swarm intelligent algorithm called Ant Colony Optimization (ACO) and verified with Genetic Algorithm (GA). A benchmark model of a simply supported plate with attached piezoelectric patches is taken to demonstrate this study. Analytical model of the simply supported plate with piezoelectric patches is derived using thin plate theory.